Environmental public health communication to engage stakeholders and foster social capacity in poorly involved communities living in industrial contaminated sites: the case study of Porto Torres (Italy) - Marsili, Daniela; Pasetto, Roberto; Iavarone, Ivano (Frontiers in Communication, 2023)
This work aims to discuss the implementation of a communication plan as a key element of the epidemiological study to foster social capacity in the scarcely involved community of the industrial contaminated site of Porto Torres (Sardinia region, Italy). We established an inter-institutional working group committed to developing communication activities and materials ensuring multidisciplinary skills from social and communication sciences to collaborate with the environmental and health experts involved in the epidemiological study. The adopted methodological approach and communication strategy resulted in effective and successful engagement of local institutional and social actors in the design and implementation of targeted communication activities.Designing and implementing environmental public health communication processes with poorly involved communities residing close to industrially contaminated sites is critically important. In these areas, environmental noxious exposures associated with high health risks are frequently combined with low socioeconomic conditions. This calls upon mechanisms of environmental injustice, distributive and procedural, and emphasizes the need to prioritize interventions based on integrative strategies securing local communities' engagement through informed participation.Based on the lessons learned in this community-focused experience in Italy, we have identified key actions for suitable environmental public health communication to foster social capacity and promote procedural environmental justice in communities living in other industrial contaminated sites.